Management of the Water Park Tourist Attraction in Soputa Village by the Village-Owned Enterprise (Bumdes) Al-Ikhlas, South Bolaang Mongondow Regency - Buange, Sri Pesriani; Gobel, Lisda Van; Kadir, Jusrin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research that the researchers want to achieve in this research is to find out by getting an overview of the Management of the Water Park Tourism Object in Soputa Village by Bumdes Al-Ikhlas, South Bolaang Mongondow Regency. State the process carried out, and In this research, the author uses qualitative descriptive to reveal in more depth about the Management of the Water Park Tourist Attraction in Soputa Village by Bumdes Al-Ikhlas for 3 Months from April to June. The results of the research show that overall the management of the water park tourist attraction by BUMDes Al-Iklas in Soputa Village, Helumo District, South Bolaang Mongondow Regency has not been optimal in terms of Facility Planning, Promotion Implementation and Government Supervision.